Scoping Review: Hubungan Pemberian Immunomodulator (Interferon Beta-1A) dengan Manifestasi Klinis Pasien COVID-19 - Azmi Azkiatul Fikri; Maya Tejasari; Listya Hanum Siswanti (Bandung Conference Series: Medical Science, 2022)
Abstract. COVID-19 causes various clinical manifestations ranging from asymptomatic, mild, moderate to severe which is characterized by the presence of sepsis, septic shock and Acute Respiratory Distress Syndrome (ARDS) which is believed to be due to a cytokine storm. COVID-19 patients experience an imbalanced immune response including weak production of type-1 interferon (IFN-Is) and the presence of a cytokine storm with relatively high levels of IL-6. Interferon α or β and IL-6 receptor monoclonal antibodies namely Tocilizumab and Sarilumab are immunomodulators recommended by the World Health Organization (WHO) and the National Institutes of Health (NIH). Aims of this research to understand the role of immunomodulators (Interferon Beta-1A) in influencing the outcome of COVID-19 patients. This research uses the method scoping review of the three databases; Pubmed Mesh, Science Direct, and Springerlink and carried out critical appraisal was using the JBI Critical Appraisal Checklist for Randomized Controlled Trials. The results of this study obtained six articles eligible. Combined use of interferon β-1a with Lopinavir or Ritonavir or Atanazavir or Ritonavir plus Hydroxychloroquine and interferon β-1a alone has a significant effect on clinical manifestations of COVID-19 patients including symptom reduction, improvement in symptoms of shortness of breath and total BCSS score (The Breathlessness, Cough and Sputum Scale), reduction in the development of patient comorbidities (odds of severe disease or death), decreased overall 28-day mortality and increased discharge rates at day 14. Abstrak. COVID-19 menimbulkan berbagai manifestasi klinis mulai dari tidak bergejala, ringan sampai sedang hingga berat yang ditandai dengan adanya sepsis, syok sepsis dan Acute Respiratory Distress Syndrome (ARDS) yang dipercaya akibat adanya badai sitokin. Pasien COVID-19 mengalami ketidakseimbangan respon imun diantaranya lemahnya produksi interferon tipe-1 (IFN-Is) dan adanya badai sitokin dengan kadar IL-6 relatif tinggi. Interferon α atau β serta IL-6 receptor monoclonal antibodies yakni Tocilizumab dan Sarilumab merupakan immunomodulator yang direkomendasikan oleh World Health Organization (WHO) dan National Institutes of Health (NIH). Tujuan penelitian ini untuk memahami peranan immunomodulator (Interferon Beta-1A) dalam memengaruhi hasil klinis pasien COVID-19. Penelitian ini menggunakan metode scoping review dari tiga database; Pubmed Mesh, Science Direct, dan Springerlink serta dilakukan critical appraisal menggunakan JBI Critical Appraisal Checklist for Randomized Controlled Trials. Hasil penelitian ini didapatkan enam buah artikel yang eligible. Penggunaan kombinasi interferon β-1a dengan Lopinavir atau Ritonavir atau Atanazavir atau Ritonavir ditambah Hidroksiklorokuin serta interferon β-1a tunggal berpengaruh signifikan terhadap manifestasi klinis pasien COVID-19 meliputi pengurangan gejala, perbaikan gejala sesak nafas dan total skor BCSS (The Breathlessness, Cough and Sputum Scale), pengurangan perkembangan komorbid penyakit pasien (odds of severe disease or death), penurunan angka keseluruhan mortalitas 28 hari dan peningkatan tingkat kepulangan pada hari ke 14.